Evaluation of non-infectious causes of acute encephalopathy in the pediatric patients (Annals of Medical Research, 2022)
Aim: The aim of the study is to evaluate and classify the less common non-infectious causes of acute encephalopathy (AE).Materials and Methods: The clinical, etiological, radiological and electrophysiological findings of the patients who were diagnosed with AE were analyzed retrospectively. The patients were classified using the flow chart of the new evidence-based guidelines for AE.Results: Noninfectious causes were identified in 22 of 45 (%48) patients diagnosed with AE[ %49.8 were male]. Mean age of patients was found 3.4±4.6 (0-17.5) years. Seven  (%31.8) patients had status epilepticus and prolonged seizures, five patient (%22.7) had asphyxia and stroke, four patient (%18.1) had metabolic encephalopathy, two (%0.9)  had AE due to cytokine storm, two (%0.9) had autoimmunity-related AE, and two had intoxication as the cause.Conclusion: Acute encephalopathy (AE)  is a neurologic emergency condition with high morbidity and mortality. The etiology of AE covers a broad spectrum. Since treatment depends on the underlying etiology, time is of essence for diagnosis. Following an established algorithm greatly facilitates diagnosis and treatment.